Odnalezione wiersze Elżbiety Drużbackiej z manuskryptu BN akc. 11696. Komunikat - Kalamon, Ilona (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The focus of this article is a manuscript entitled “The Union of Lithuanian Nobility against the Sapieha Family in 1700 in gloria, or the battle of Olkieniki in verse described by Korytyński,” reference no. BN acc. 11696, stored at the National Library in Warsaw. The manuscript includes works by Elżbieta Drużbacka, an 18th-century poet, and was long considered lost. Known as the “Herburt Manuscript,” the artifact contains 16 works by Drużbacka, including eight completely unknown to modern readers. The text discusses the poet’s works preserved in the manuscript, the publishing history of titles known from other printed sources, and stipulates next steps to be taken in the research process.